Menilai Kesiapan Sumber Daya Manusia Untuk Mendukung Pengembangan Dunia Industri Pariwisata Di Destinasi Super Premium Labuan Bajo - andy Iwan Iswanto (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2022)
The purpose of this research is to assess the readiness of human resources in order to support the development of the tourism industry in the super premium destination Labuan Bajo and the quality of the resources needed to support the development of the tourism industry. This research uses a qualitative research design by conducting oral and written interviews with leaders of tourism actors, leaders in government agencies and communities in Labuan Bajo. The results of this research are that human resources in Labuan Bajo must be continuously improved so that they can be more ready to work in the tourism industry. Besides that, it is also important to improve the quality of service with the principles of excellent service so that the tourism industry in Labuan Bajo can have a positive impact on the development and welfare of the community.